2012
DOI: 10.1017/s1368980012003783
|View full text |Cite
|
Sign up to set email alerts
|

Relative validation of a quantitative FFQ for use in Brazilian pregnant women

Abstract: Objective: To evaluate the ability of an FFQ, designed for use in Brazilian pregnant women, to estimate nutrient intakes during pregnancy. Design: A prospective study was conducted among 103 pregnant women attended by the Brazilian national health-care service. Food intake during pregnancy was evaluated by three 24 h dietary recalls (24hR), one per trimester of pregnancy, and also by two FFQ. The FFQ with eighty-five food items included questions about frequency of intake and portion sizes during two periods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 24 publications
(50 reference statements)
4
39
2
3
Order By: Relevance
“…First, the cross-sectional design of the study does not allow for establishing causal relationships. Also, the FFQ previously validated for adults (20) was not developed for pregnancy; however, epidemiological studies have shown that FFQ can be used to measure nutritional dietary intake during pregnancy with acceptable validity and reproducibility (7,10) , including in Brazil (37) . Finally, the 0·018 0·471 − 0·031, 0·067 0·035 0·169 − 0·014, 0·084 0·033 0·180 − 0·015, 0·080 Family income ($US) † 0·0003 0·007 0·0001, 0·0005 0·0001 0·259 − 0·0001, 0·0003 − 0·0003 0·025 − 0·0005, 0·0003 Parity (n) − 0·083 0·041 − 0·163, −0·003 − 0·015 0·715 − 0·095, 0·065 0·142 <0·001 0·065, 0·219 Marital status 0·023 0·688 − 0·090, 0·136 0·002 0·977 − 0·111, 0·115 0·125 0·026 0·015, 0·236 Skin colour 0·015 0·761 − 0·084, 0·114 − 0·026 0·600 − 0·125, 0·072 0·021 0·678 − 0·077, 0·118 Adjusted Age (years) 0·021 0·058 − 0·001, 0·042 − 0·017 0·075 − 0·037, 0·003 − 0·018 0·061 − 0·037, 0·001 Schooling (years) 0·019 0·406 − 0·026, 0·065 0·025 0·132 − 0·018, 0·067 0·010 0·628 − 0·030, 0·050 Family income ($US) † 0·0006 0·011 0·0001, 0·001 0·0004 0·090 − 0·0001, 0·001 − 0·0004 0·102 − 0·001, 0·0001 Parity (n) − 0·097 0·030 − 0·184, −0·009 0·007 0·861 − 0·074, 0·089 0·098 0·012 0·021, 0·175 Marital status ‡ 0·030 0·588 − 0·078, 0·137 0·0004 0·993 − 0·100, 0·101 0·073 0·131 −0·022, 0·168 *The models were adjusted for total energy intake and pre-gestational BMI.…”
Section: Discussionmentioning
confidence: 99%
“…First, the cross-sectional design of the study does not allow for establishing causal relationships. Also, the FFQ previously validated for adults (20) was not developed for pregnancy; however, epidemiological studies have shown that FFQ can be used to measure nutritional dietary intake during pregnancy with acceptable validity and reproducibility (7,10) , including in Brazil (37) . Finally, the 0·018 0·471 − 0·031, 0·067 0·035 0·169 − 0·014, 0·084 0·033 0·180 − 0·015, 0·080 Family income ($US) † 0·0003 0·007 0·0001, 0·0005 0·0001 0·259 − 0·0001, 0·0003 − 0·0003 0·025 − 0·0005, 0·0003 Parity (n) − 0·083 0·041 − 0·163, −0·003 − 0·015 0·715 − 0·095, 0·065 0·142 <0·001 0·065, 0·219 Marital status 0·023 0·688 − 0·090, 0·136 0·002 0·977 − 0·111, 0·115 0·125 0·026 0·015, 0·236 Skin colour 0·015 0·761 − 0·084, 0·114 − 0·026 0·600 − 0·125, 0·072 0·021 0·678 − 0·077, 0·118 Adjusted Age (years) 0·021 0·058 − 0·001, 0·042 − 0·017 0·075 − 0·037, 0·003 − 0·018 0·061 − 0·037, 0·001 Schooling (years) 0·019 0·406 − 0·026, 0·065 0·025 0·132 − 0·018, 0·067 0·010 0·628 − 0·030, 0·050 Family income ($US) † 0·0006 0·011 0·0001, 0·001 0·0004 0·090 − 0·0001, 0·001 − 0·0004 0·102 − 0·001, 0·0001 Parity (n) − 0·097 0·030 − 0·184, −0·009 0·007 0·861 − 0·074, 0·089 0·098 0·012 0·021, 0·175 Marital status ‡ 0·030 0·588 − 0·078, 0·137 0·0004 0·993 − 0·100, 0·101 0·073 0·131 −0·022, 0·168 *The models were adjusted for total energy intake and pre-gestational BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Uma elevada proporção de gestantes (>70%) foi classificada no mesmo quartil ou quartis adjacentes para estimativa de energia, carboidratos, cálcio, potássio, fibra, zinco, colesterol e vitaminas A, riboflavina, niacina, C, E e ácido fólico, quando comparado a estimativa de três IR 24hs ao longo da gestação. 7 Para avaliação da reprodutibilidade, o QQFA foi aplicado em duplicata por um mesmo entrevistador, com intervalo médio de 15-45 dias entre cada aplicação. As gestantes foram solicitadas a responder o tamanho da porção e frequência de consumo da lista de alimentos desde o início da gestação.…”
Section: Métodosunclassified
“…These correlations were somewhat lower than those reported in our study for solid fruits (0.52) and total vegetables (0.44); however, our correlations for meat, poultry, fish (we did not assess red meat separately (0.31)) were lower. Our results are also comparable to those reported by other researchers for validation of diet screeners or much longer FFQs among pregnant women (Erkkola et al., 2001; Mouratidou, Ford, & Fraser, 2006; Brantsaeter, Haugen, Alexander, & Meltzer, 2008; Loy, Marhazlina, Nor, & Hamid, 2011; Barbieri, Nishimura, Crivellenti, & Sartorelli, 2013; Barbieri , Crivellenti, Nishimura, & Sartorelli, 2014). For example, Brantsaeter et al.…”
Section: Discussionmentioning
confidence: 99%